Templating polyacrylamide hydrogel for interconnected microstructure and improved performance. Issue 17 (11th January 2018) - Bassil, Maria; El Haj Moussa, Georges; El Tahchi, Mario
ABSTRACT: In this study, the pressure and temperature are monitored during acrylamide polymerization and their effects on the mechanical properties and swelling of the resulting hydrogel are investigated. The polymerization kinetic and network formation mechanism are correlated to the environmental thermodynamic conditions under which the hydrogels are polymerized. Then, the swelling and Young's modulus are measured and shown to be tunable along a wide range of values. The swelling ratio varies between 50 and 2262 while Young's modulus varies between 10.99 and 40.70 kPa. In addition, the formation of macroporous hydrogel with channel like structures along the vacuum direction under a reduced pressure of 5 mbar is reported. The macroporous hydrogel has a modulus of 40.70 kPa and shrink approximatively three times faster than the hydrogel polymerized under normal pressure and has a modulus of 10.99 kPa. Hence, this interconnected network can overcome the fluid diffusion limitations of bulk hydrogels without compromising the mechanical properties. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46205. Abstract :